If I understand your question correctly I would say X= 3pi/4.
In which people move all of the terms containing tan X to the left side of the equation.
You’ll get, 3tan(X) + 6 = 3
Move all of the terms not containing tan (X) to the right side of the equation.
3tan (X) = -3
Then divide each term by three and simplified.
Tan (X) = -1
Take the inverse tangent of both sides of the equation to extract X from inside the tangent.
X = arctangent (-1)
The exact value of arctangent (-1) is
- pi/4.
The tangent function is negative in the second and fourth quadrants. To find the second solution, subtract the reference angle from pi to find the solution in the third quadrant.
X = - pi/4 - pi
Simplify the expression to find the second solution.
X = 3pi/4
I hope that helps.